Upaya Meningkatkan Aktivitas dan Hasil Belajar Sejarah Dengan Menggunakan Pendekatan Inkuiri Pada Siswa SMA Negeri 1 Metro - Siti Erlina (Jurnal Dewantara, 2019)
This study aims to increase activity and sejarah student learning outcomes through inquiry learning approach. Places that are used in this study were high school Negeri 1 Metro, amounting to 23 students.This type of study is a descriptive qualitative research methods class action. The results obtained in this study show that: 1) Average activity in cycle I (48.73%) increased by 14.92% in cycle II (63.65%), 2) Improved student learning outcomes of the cycle I to the second cycle of 28.57% from 57.14% to 85.71% cycle I to cycle II on the subject of sejarah. Based on these results, the suggestions can be submitted are: to improve the quality of teachers should be teaching sejarah in the inquiry learning approach. Learning by using the inquiry approach related to learning outcomes and learning processes, and are expected to contribute to the awakening of science and technology.